Teacher's Specialized Content Knowledge on the Concept of Square: A Vignette Approach - Budiarto, Mega Teguh; Fuad, Yusuf; Sahidin, Latief (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2021)
In learning geometry, the discussion about the definition of quadrilateral is a material that is difficult and not easily taught by the teacher. This study aims to explore the teacher's specialized content knowledge about square. This is a descriptive-qualitative research. The process of selecting subjects begins with searching prospective subject data according to the level of the teacher through a portfolio of 82 teachers in South East of Sulawesi: (33 First Teachers, 33 Young Teachers, and 16 Intermediate Teachers). The research subjects consisted of three teachers, namely: First Teacher, Young Teacher dan Intermediate Teacher with score > 50. Data were taken using vignette. The results show that there is a difference when the teacher is asked to define a square with when given a definition of a square. First Teacher is accurate when given a square definition with the symmetry and diagonal axis attributes; the side attribute is not accurate in giving arguments to the square definition. Young Teacher is inaccurate when given the definition of a square with side and angle attributes; accurate with symmetry and diagonal axis attributes; but it is not accurate when given a square definition. Regarding attributes of side; Intermediate Teacher revealed that the side and angle attributes are inaccurate but accurate with the symmetry and diagonal axis attributes but do not appear / are not used when asked to define a square. Specialized content knowledge First Teacher is better because it has been able to reconstruct concepts from a square, but Young Teacher and Intermediate Teacher are still influenced by concept images and figural concepts. DOI: https://doi.org/10.22342/jpm.15.2.11653.1-22